2020
DOI: 10.1177/0011128720950024
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Victimization, Mental Health Problems, and Disabilities on Juvenile Justice Processing: Does Gender Matter?

Abstract: Victimization, mental health problems, and disabilities are associated with an increased likelihood of delinquent behavior, and girls in the juvenile justice system report higher rates of past trauma and victimization, sexual abuse, and mental health issues than boys. However, the influence of these problems on juvenile justice processing remains understudied. This study investigated the impact of victimization, mental health problems, disabilities, and comorbidity on intake and adjudication decisions across g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 76 publications
(124 reference statements)
0
5
0
1
Order By: Relevance
“…Attention to girls who have suffered trauma and abuse during their developmental childhood stages or in juvenile correctional facilities is critical to minimize the likelihood of repeated traumatization. As suggested by Terry and Williams (2019), neglected traumatic experiences among girls during adolescence can escalate to other, more severe disorders and delinquent behaviors (Chappell & Maggard, 2021). Therefore, a second recommendation of gender-responsive programming is to recognize that trauma is a common trait among incarcerated girls in the United States and Costa Rica (Zettler, 2021).…”
Section: Implications and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Attention to girls who have suffered trauma and abuse during their developmental childhood stages or in juvenile correctional facilities is critical to minimize the likelihood of repeated traumatization. As suggested by Terry and Williams (2019), neglected traumatic experiences among girls during adolescence can escalate to other, more severe disorders and delinquent behaviors (Chappell & Maggard, 2021). Therefore, a second recommendation of gender-responsive programming is to recognize that trauma is a common trait among incarcerated girls in the United States and Costa Rica (Zettler, 2021).…”
Section: Implications and Recommendationsmentioning
confidence: 99%
“…Unresolved trauma and abuse during the developmental stages of childhood and adolescence can manifest into mental health disabilities such as anxiety, depression, post-traumatic stress disorder (PTSD), and anti-social behaviors (Kerig et al, 2009; Terry & Williams, 2019; Zahn et al, 2010). For many girls, delinquent behaviors like truancy, running away from home, and substance abuse are a direct response to this trauma and abuse (Belknap & Holsinger, 2006; Chappell & Maggard, 2021). For example, studies have found that girls in the United States who repeatedly run away from home are more likely to be victims of sexual and physical abuse (Shufelt & Cocozza, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…From a public health perspective, it is important to understand young prisoners¨mental health and well-being and to identify what kind of support they need to improve their current and future situations (Ruiz-I ´n ˜iguez et al, 2021). Without a supportive environment and access to operating quality services, deterioration of the mental health and well-being of young prisoners might have substantial negative effects on their social and physical situation in the prisons (Chappell and Maggard, 2021). In addition, these negative impacts may continue into their adulthood and significantly affect their well-being, including their education and career (Seker et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…While literature examining delinquency and externalizing problems of youth in juvenile detention centers is relatively extensive (Docherty et al, 2016; Salbach-Andrae et al, 2009), research on the development of internalizing symptoms within this marginalized population is scarce. Yet, literature suggests that over 20 per cent of youth in juvenile detention centers exhibit internalizing problems (Teplin et al, 2002) and over 40 per cent of detained youth endorse comorbid internalizing and externalizing symptoms (Chappell and Maggard, 2020; Goldstein et al, 2003; Mallett, 2014). Recent research suggests a bidirectional association between internalizing symptoms and youth engagement in delinquent and offending behaviors (Jolliffe et al, 2019; Kofler et al, 2011).…”
mentioning
confidence: 99%